Effects of text messaging in addition to emails on physical activity among university and college employees in the UK. (April 2013) - Suggs, Suzanne; Blake, Holly; Bardus, Marco; Lloyd, Scott
Objectives: To test the effects of adding text messages to weekly email communications on recipients' total physical activity (leisure-time; workplace; domestic and garden; and active transportation) in employees of universities and colleges in the UK. Methods: A randomised trial with two study groups (email only or email plus text messaging for 12 weeks) was implemented at five workplaces. Data were collected at baseline, immediately after, and four weeks after the intervention. Intervention effects on physical activity were evaluated using latent growth modelling. Results: Total physical activity decreased over time in both groups but the decrease was non-significant. The only significant difference between groups was found for workplace physical activity, with the group receiving emails and text messages having a linear decrease of 2.81 Metabolic Equivalent h/week ( β = −0.31, p = 0.035) compared to the email only group. Conclusions: Sending employees two additional text messages resulted in less physical activity. Further investigation is needed to understand whether text messaging may play a beneficial role in promoting physical activity in workplace settings.